Wanprestasi In Sharia Economic Disputes: Implementation Of Sharia Principles In Religious Court Judges' Decisions On The Ijaroh Muntahiyah Bi Al-Tamlik Agreement - Nuroniyah; Oyo Sunaryo Muchlas; Ramdani Wahyu Sururie (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2026)
This study examines the current issue regarding default (customer negligence in sharia financing contracts), particularly in the AkadIjarah Muntahiyah bi al-Tamlik(IMBT), and analyze how the Religious Court (PA) implements sharia principles in its decisions on disputes. IMBT combines rent (lease) and the promise of transfer of ownership (completeness), often giving rise to disputes when customers fail to fulfill their installment payment obligations. The central issue is the harmonization between General Civil Law (especially the concepts of compensation and execution) and Sharia Economic Law (especially the principle of avoidingribaand achieve justiceshulh). The method used in this research is normative legal research which is analytical-descriptive in nature. The approach used in this research is the Legislation approach (Statute Approach). The research results indicate challenges in the application of sanctions due to default. Judges' decisions are required to not only be based on formal legal certainty but also reflect sharia values, such as avoiding fines that areusuryand considering the customer's good faith. This study concludes that the implementation of sharia principles in judicial decisions in IMBT default cases still requires consistency and stricter guidance from the Supreme Court to ensure substantive justice and sharia compliance for all parties.